Manajemen Pembinaan Guru dalam Meningkatkan Mutu Pendidikan di Kota Subulussalam - Merawati; Emilda Sulasmi; Faisal Rahman Dongoran (JoIEM (Journal of Islamic Education Management), 2024)
This study aims to analyze the planning, implementation and results of teacher coaching management in an effort to improve the quality of education in Subulussalam City. The approach used was qualitative with a descriptive type. Data were collected through observation, interviews and documentation, while data analysis was conducted through: data reduction, data presentation, and conclusion drawing. The research results include: (1) Planning for coaching by the Subulussalam City Education and Culture Office is not yet fully in accordance with level qualifications, focusing on improving teacher quality through short, medium and long term planning, as well as partnerships. (2) The implementation of the teacher quality improvement program is carried out through training according to level, both by the Office independently and through partnerships. (3) This coaching results in improved teacher competence, motivation and enthusiasm for teaching, performance monitoring, implementation of best practices and understanding of education policy.